FEM Study of Induction Machines Suffering from Rotor Electrical Faults Using Stray Flux Signature Analysis - Panagiotou, P. A.; Arvanitakis, I.; Lophitis, Neophytos; Gyftakis, K. N. (My University, 2018)
The wide range of applications using induction machines has been enhanced with the rapid evolution of condition monitoring and variable speed drives. The latter two, along with their constantly growing demands, have raised the necessity of new approaches and techniques in fault diagnostics. A reliable solution to this matter, has proven to be the monitoring of stray magnetic flux. Accounted for in different locations on the machine's peripheral area and with different measurement techniques, the stray flux provides valuable information for fault detection and identification. This paper aims to apply one of these diagnostic strategies and the related measurement of stray flux using FEM, to evaluate its performance and diagnostic capability on two machines of different size and power rating and conclude on the quantitative effectiveness of such strategies.
Keywords: Condition monitoring; Flux sensors; Induction machines; Stray flux